Krisis Orientasi Moral Global dan Tawaran Etika Islam: Telaah Filosofis Kritis Prespektif Murtadha Muthahhari - Kurniansyah, Muhammad; Harun, Hamza; Santalia, Indo (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
The global moral orientation crisis constitutes a fundamental problem in contemporary human life, characterized by moral relativism, instrumental rationality, and the erosion of transcendent ethical purpose. Morality is increasingly reduced to pragmatic normative mechanisms detached from questions of meaning and human essence. This article aims to examine the global moral crisis and to articulate an Islamic ethical response through a critical philosophical analysis of Murtadha Muthahhari’s thought. Employing a qualitative library research approach, this study utilizes descriptive-analytical and critical-philosophical methods. The analysis demonstrates that the global moral crisis originates from a flawed understanding of human beings as entities detached from ontological and existential orientation. Through the concept of ethical fitrah, Muthahhari affirms that moral values possess an objective foundation inherent in human nature, thereby offering a critique of moral relativism without negating cultural plurality. Furthermore, the Islamic ethical orientation toward human perfection (kamal al-insan) frames morality as a transformative process integrating rationality, spirituality, and social responsibility. Accordingly, Islamic ethics emerges as a rational, humanistic, and relevant moral framework capable of responding to the challenges of the contemporary global moral crisis.